2023
DOI: 10.3389/fimmu.2023.1115272
|View full text |Cite
|
Sign up to set email alerts
|

By integrating single-cell RNA-seq and bulk RNA-seq in sphingolipid metabolism, CACYBP was identified as a potential therapeutic target in lung adenocarcinoma

Abstract: BackgroundLung adenocarcinoma (LUAD) is a heterogeneous disease with a dismal prognosis for advanced tumors. Immune-associated cells in the microenvironment substantially impact LUAD formation and progression, which has gained increased attention in recent decades. Sphingolipids have a profound impact on tumor formation and immune infiltration. However, few researchers have focused on the utilization of sphingolipid variables in the prediction of LUAD prognosis. The goal of this work was to identify the major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 55 publications
(36 reference statements)
0
25
0
Order By: Relevance
“…Sphingolipids are known to play a crucial role in tumor growth and its interactions with various pathways related to cancer (60-65). However, many genes associated with sphingolipids remain poorly understood and have not been extensively researched as potential therapeutic targets in clinical settings (66,67). We identified six genes that form a strong risk score signature.…”
Section: Discussionmentioning
confidence: 99%
“…Sphingolipids are known to play a crucial role in tumor growth and its interactions with various pathways related to cancer (60-65). However, many genes associated with sphingolipids remain poorly understood and have not been extensively researched as potential therapeutic targets in clinical settings (66,67). We identified six genes that form a strong risk score signature.…”
Section: Discussionmentioning
confidence: 99%
“…6 It performs an integral function in LUAD progression with significant heterogeneity. 7 Evidence confirmed that P2RY14 may be involved in LUAD immune invasion and inhibit tumor cell immune 下Áescape within LUAD microenvironment. 8 A significant impact of JAML expression on LUAD prognosis and TME was observed, which highlights the importance of TME on LUAD patients.…”
mentioning
confidence: 84%
“…Tumor microenvironment (TME) refers to the surrounding environment including tumor cells, immune cells, and stromal cells 6 . It performs an integral function in LUAD progression with significant heterogeneity 7 . Evidence confirmed that P2RY14 may be involved in LUAD immune invasion and inhibit tumor cell immune 下·escape within LUAD microenvironment 8 .…”
Section: Introductionmentioning
confidence: 99%
“…We employed the “seurat” and “singleR” R packages to perform quality control on scRNA-seq data ( 20 ). To ensure the data’s accuracy, we eliminated genes expressed in less than three single cells, cells with less than 200 or more than 7,000 genes, and cells with more than 10% mitochondrial genes.…”
Section: Methodsmentioning
confidence: 99%